Perceptions of Physiotherapists in Relation to Spiritual Care - Turner, Helen (Journal for the Study of Spirituality, 2016)
Few studies have examined the perceptions of health professionals towards spiritual care in the UK despite recent policies from the National Health Service (NHS) surrounding spiritual care provision. To the authors' knowledge, no studies have examined the perceptions of physiotherapists either in the UK or worldwide. The aim of this study was to examine the perceptions of Scottish physiotherapists in relation to spirituality and spiritual care in health care, including the role of spirituality in health, barriers to spiritual care provision, and training. Questionnaires were sent to Physiotherapy Departments in all 14 NHS Trusts in Scotland in order to achieve a representative random sample from across Scotland. There was participation from all 14 Trusts with participants self-selecting to complete the questionnaire. A 30% response rate (274/916) was achieved. All returned questionnaires were completed with minimal or no omissions. The majority of physiotherapists agreed that spirituality is an important aspect of health care and that some level of spiritual care is appropriate to physiotherapy. Lack of training and confusion over the role of physiotherapists in spiritual care provision were also highlighted. The main barriers identified by the sample were lack of training or experience, uncertainty over managing spiritual issues, and lack of time. The study concludes that physiotherapists need guidance over their expected role in spiritual care provision, and adequate training in order to fulfil this role. Referral pathways to specialist spiritual care services need to be made clearer and more accessible.